2000
DOI: 10.1023/a:1008387800525
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic secretory breast cancer. Non-responsiveness to chemotherapy: Case report and review of the literature

Abstract: Secretory carcinoma of the breast is a rare and indolent tumour originally described in children but occurring equally in the adult population. The principal management problems following primary surgical treatment are local recurrence and axillary lymph node metastases. Distant metastases are extremely rare. We present the case of a 27-year-old woman with pulmonary metastases from a secretory breast cancer treated by mastectomy and axillary lymph node dissection 12 years previously. There was no response to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
0
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 12 publications
4
100
0
7
Order By: Relevance
“…22 Previous published series and case reports indicated that secretory breast carcinoma is associated with a more favorable outcome than other subtypes of invasive breast carcinomas. 11 However, more recent studies have showed that outcome is age-related.…”
Section: Discussionmentioning
confidence: 99%
“…22 Previous published series and case reports indicated that secretory breast carcinoma is associated with a more favorable outcome than other subtypes of invasive breast carcinomas. 11 However, more recent studies have showed that outcome is age-related.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally termed 'juvenile breast cancer' by McDivitt and Stewart in 1966, because the only known patients were children or very young women. [1][2][3] However, subsequent studies have included many adult patients, including a substantial number of postmenopausal women, so much so that approximately two-thirds of the almost 100 published cases have been in adults. Consequently, the term juvenile breast cancer has been replaced by the more descriptive 'secretory breast cancer' (SBC).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the term juvenile breast cancer has been replaced by the more descriptive 'secretory breast cancer' (SBC). 3,4 The tumour can occur anywhere in the breast. It frequently presents as a mobile, well-circumscribed, subareolar mass, sometimes simulating fibroadenoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distant spread is extremely rare, but when it occurs chemo-resistance, leading to adverse prognosis and dismal outcome, should be suspected. However, patients with secretory carcinomas, in contrast to stage-matched ductal counterparts, have better survival [6]. Despite all favorable features, adequate surgical treatment consists of mastectomy, rather than local excision [1,[7][8][9].…”
Section: Discussionmentioning
confidence: 99%